Dimensions éthiques de l’allocation du financement international de l’adaptation au changement climatique - Romain Weikmans (VertigO)
The issue of interstate distribution of financial resources provided under the United Nations Framework Convention on Climate Change (UNFCCC) to support adaptation in developing countries has attracted considerable attention both in academic circles and in international negotiations. Which parameters should guide the allocation of these financial resources? Considerations of equity and efficiency are present in the text of the UNFCCC (1992) and in various decisions taken by the Conference of the Parties to the Convention. However it is apparent that notions of equity prevail in these texts regarding the allocation of adaptation funding. For some observers, this pre-eminence of equity issues comes from the difficulties in assessing the effectiveness of adaptation actions. It is right that significant uncertainties plague projections of climate change, exposure pathways and vulnerabilities. However, and as we discuss in this article, the assessment of countries’ vulnerabilities – i.e., the assessment of their adaptation needs – is equally complex. In our view, the focus on equity issues in the allocation of international adaptation finance should rather be understood as a reflection of ethical choices. This article aims at (i) highlighting these normative choices; and (ii) examining how they unfold in the allocative practices of dedicated multilateral climate funds.